1974
DOI: 10.1037/h0036190
|View full text |Cite
|
Sign up to set email alerts
|

Proxemic behavior of primary school children as a function of their socioeconomic class and subculture.

Abstract: Two field studies were reported. In Study 1, pairs of lower-class black school children and white school children were photographed conversing in a school yard, and interaction distances between dyad members were computed using a new photogrammetric technique. Ten judges also rated photographs for interaction distance. Results by both methods indicated no differences between subcultures. Study 2 explored the effects of subculture and socioeconomic class on interaction distance. Middle-class children were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…For example, Willis (1966) found that blacks greet other blacks at further distances than whites greet other whites, whereas Baxter (1970) in comparing three subcultural groups on personal space, found that blacks stood the furthest apart, Anglo-Americans the next furthest, and Mexicans took the most mediate distances. The results on proxemic variations are equivocal, however, as Scherer (1974) found, when comparing lower-and middle-class black and white children, that interpersonal distances were a function of class and not ethnic grouping. With respect to cultural variations in gaze behavior, the evidence is only suggestive.…”
mentioning
confidence: 90%
“…For example, Willis (1966) found that blacks greet other blacks at further distances than whites greet other whites, whereas Baxter (1970) in comparing three subcultural groups on personal space, found that blacks stood the furthest apart, Anglo-Americans the next furthest, and Mexicans took the most mediate distances. The results on proxemic variations are equivocal, however, as Scherer (1974) found, when comparing lower-and middle-class black and white children, that interpersonal distances were a function of class and not ethnic grouping. With respect to cultural variations in gaze behavior, the evidence is only suggestive.…”
mentioning
confidence: 90%
“…Unobtrusive observation, often accompanied by still or motion pictures (e.g., Baxter, 1970;Dabbs & Stokes, 1975;Jones, 1971;Nesbitt & Steven, 1974;Scherer, 1974), is fully naturalistic but allows the researcher minimal control of subjects. By prearranging collaborating assistants in hallways, on sidewalks, or in queues, one can contrive situations with which to confront unsuspecting subjects.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…With one major exception (Blurton Jones, 1972), the child in school has not been featured as the subject for attention in books on nonverbal interaction. There have been articles on the use of personal space by school children (Scherer, 1974), but only one article (Chaikin, Sigler, & Derlega, 1974) has dealt with the more subtle aspects of teacher-pupil nonverbal interaction.…”
Section: Horementioning
confidence: 99%